Division-Based, Growth Rate Diversity in Bacteria - Gangwe Nana, Ghislain Y.; Ripoll, Camille; Cabin-Flaman, Armelle; Gibouin, David; Delaune, Anthony; Janniere, Laurent; Grancher, Gerard; Chagny, Gaelle; Loutelier-Bourhis, Corinne; Lentzen, Esther; Grysan, Patrick; Audinot, Jean-Nicolas; et al. (Frontiers in Microbiology, 2018)
To investigate the nature and origins of growth rate diversity in bacteria, we grew Escherichia coli and Bacillus subtilis in liquid minimal media and, after different periods of 15N-labeling, analyzed and imaged isotope distributions in individual cells with Secondary Ion Mass Spectrometry. We find a striking inter- and intra-cellular diversity, even in steady state growth. This is consistent with the strand-dependent, hyperstructure-based hypothesis that a major function of the cell cycle is to generate coherent, growth rate diversity via the semi-conservative pattern of inheritance of strands of DNA and associated macromolecular assemblies. We also propose quantitative, general, measures of growth rate diversity for studies of cell physiology that include antibiotic resistance.